2018
DOI: 10.3389/fneur.2018.00072
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hypopituitarism Associated with Increased Postconcussive Symptoms Is Prevalent after Blast-Induced Mild Traumatic Brain Injury

Abstract: The most frequent injury sustained by US service members deployed to Iraq or Afghanistan is mild traumatic brain injuries (mTBI), or concussion, by far most often caused by blast waves from improvised explosive devices or other explosive ordnance. TBI from all causes gives rise to chronic neuroendocrine disorders with an estimated prevalence of 25–50%. The current study expands upon our earlier finding that chronic pituitary gland dysfunction occurs with a similarly high frequency after blast-related concussio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 111 publications
(101 reference statements)
2
33
0
2
Order By: Relevance
“…A military survey of soldiers returning from Iraq reported 44% of troops who had sustained mild TBIs with loss of consciousness screened positive for PTSD as compared to 16% who sustained only bodily injury ( 127 ). Additionally, a very recent study of veterans returning from dangerous posts in Iraq or Afghanistan found significant main effects of mild TBI on self-report questionnaires measuring PTSD symptoms ( 60 ). From an experimental angle, an animal study by Elder and others found that blast exposure causing mild TBI in anesthetized mice provoked PTSD-related traits, such as increased startle response (i.e., anxiety), enhanced contextual fear response, altered response in a predator scent assay, and increased expression of a protein involved in the fear response, suggesting that frank structural injury from the blast may have been the cause of the symptoms rather than memory of the event ( 120 ).…”
Section: The Mysterious Case Of Ptsdmentioning
confidence: 99%
See 2 more Smart Citations
“…A military survey of soldiers returning from Iraq reported 44% of troops who had sustained mild TBIs with loss of consciousness screened positive for PTSD as compared to 16% who sustained only bodily injury ( 127 ). Additionally, a very recent study of veterans returning from dangerous posts in Iraq or Afghanistan found significant main effects of mild TBI on self-report questionnaires measuring PTSD symptoms ( 60 ). From an experimental angle, an animal study by Elder and others found that blast exposure causing mild TBI in anesthetized mice provoked PTSD-related traits, such as increased startle response (i.e., anxiety), enhanced contextual fear response, altered response in a predator scent assay, and increased expression of a protein involved in the fear response, suggesting that frank structural injury from the blast may have been the cause of the symptoms rather than memory of the event ( 120 ).…”
Section: The Mysterious Case Of Ptsdmentioning
confidence: 99%
“…This is nonetheless speculative at this point. And yet, one aforementioned study of veterans did report intriguing results: using self-report questionnaires to investigate the relationship between TBI, overall hypopituitarism, and PTSD, the authors revealed a significant main effect of TBI-induced hypopituitarism on questionnaires assessing PTSD symptoms ( 60 ).…”
Section: The Mysterious Case Of Ptsdmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, it was reported that 31% of veterans who at least had one blast-related mild TBI developed PD, while the rate was 15% among the control group. It was stated that the symptoms of PD overlapped significantly with those of posttraumatic stress disorder (PTSD) (9). The rate of PD due to sportsrelated TBIs was reported to range from 15% to 46.6% (10).…”
Section: Pituitary Dysfunctionmentioning
confidence: 99%
“…Accumulating evidence suggests TBI impairs the hypothalamic‐pituitary‐adrenal axis, resulting in clinical manifestations resembling post‐concussive symptoms (Bondanelli et al, ; Undurti et al, ; West & Sharp, ; Wilkinson et al, ). Both acute and persistent neuroendocrine dysfunction (NED) can have a profound impact on health outcomes following mTBI.…”
Section: Introductionmentioning
confidence: 99%